The Bible in film-- the Bible and film - Exum, J. Cheryl (Brill, 2006)
Biblical scholars and students are finding the role of the Bible in film an increasingly absorbing and rewarding topic. There are films that retell biblical narratives and there are films that allude to the Bible or otherwise build on or appropriate biblical themes and images. The eleven lively and provocative articles in this volume explore both types of film, showcasing the cinema's impact on the perception of the Bible in modern culture. Originally published as issue 1-2 of Volume 14 (2006) of Brill's journal Biblical Interpretation. For more details on this journal, please click here.